Volcanic calderas and its relation to geothermal resources in southern Peru - Díaz Huaina, Guillermo Nicanor (2021)
The study area ranges from 13.8 ° to 18.3 ° south latitude of the Peruvian territory, mainly covering Tacna, Moquegua, Arequipa and part of Ayacucho, Apurímac and Puno regions. Geomorphologically it mainly covers the Western Cordillera and part of the Altiplano. Based on satellite images, regional geology information and hot springs distribution, eleven (11) calderic structures of various dimensions were determined. The geometry of the structures in some cases is determined thanks to geomorphological patterns of the volcanic environment. It was determined that in the study area, there is a wide distribution of recent lava and pyroclastic rocks, which mask the calderic structures and, on the other hand, it hides various geothermal systems. In some cases, there are geothermal manifestations on the surface, which have emerged through recent faults. The geothermal manifestations distribution coincides in many cases with the edges of the calderic structures and is controlled by structural systems, geological contacts, which intersect with the edges of said calderas. Therefore, it is concluded that in southern Peru there is a promising potential for geothermal resources, in some cases with visible surface manifestations and others hidden by recent volcanic materials.